Effect of nurse-led intervention on knowledge and preventive behavior of diabetic pregnant women regarding COVID-19 associated mucromycosis infection in mid-delta region of Egypt - Marwa A. Shahin; Mira M. Abu-Elenin; Hanan E. Nada (BMC, 2023)
Abstract Background Black fungus (mycoses) is an opportunistic invasive infection that predominantly occurred among immunosuppressed persons. It has been recently detected in COVID-19 patients. The pregnant diabetic woman is susceptible to such infections and needs recognition for protection. This study aimed to evaluate the effect of the nurse-led intervention on the knowledge and preventive practice of diabetic pregnant women regarding fungal mycosis during the COVID-19 pandemic. Method This quasi-experimental study was conducted at maternal health care centers in Shebin El-Kom, Menoufia Governorate, Egypt. The study recruited 73 diabetic pregnant women through a systematic random sampling of pregnant women attending the maternity clinic during the period of the study. A structured interview questionnaire was used to measure their knowledge regarding Mucormycosis and COVID-19 manifestations. The preventive practices were assessed through an observational checklist of hygienic practice, insulin administration, and blood glucose monitoring for the prevention of Mucormycosis infection. Results The study revealed a statistically significant increment in the participants' knowledge, preventive practice, personal hygiene, and diabetes self-care scores (9.56 ± 1.75 ,3.6 ± 1.18, 3.18 ± 1.29 post-intervention) comparable to (6.19 ± 1.66, 1.97 ± 1.35, 0.89 ± 1.38  pre-intervention) respectively. There was a significant improvement in the overall COVID-19 protective score against Mucormycosis (from 2.66 ± 1.74 to 4.53 ± 1.43). Conclusion Nursing educational sessions had a positive effect on pregnant women's awareness and preventive behavior. Hence, it is recommended to integrate nurse-led intervention targeting the preventive practice against COVID-19-associated Mucormycosis infection (CAM) as routine services for diabetic pregnant women during antenatal care.